Peranan Ampas Kopi Terhadap Pertumbuhan Tanaman Sawi (Brassica juncea L.) dan Sifat Kimia Tanah Ultisol - Muhammad Taufani Asadullah Rahman; Hairil Ifansyah; Jumar Jumar (Agroekotek View, 2021)
Coffee grounds waste is abundant and its role in plant growth is not widely known.  Therefore, this study applies coffee grounds to Ultisols to find out its role in increasing the growth of mustard greens (Brassica juncea L.) and also improving the chemical properties of Ultisols. This study used a completely randomized design method (CRD) with a single factor of coffee grounds, namely K0 (without coffee grounds), K1 (1 ton ha-1), K2 (1,5 ton ha-1), K3 (2 ton ha-1), K4 (2,5 ton ha-1), K5 (3 ton ha-1), K6 (3,5 ton ha-1), K7 (4 ton ha-1), K8 (4,5 ton ha-1) and K9 (5 ton ha-1).  The parameters observed were pH, exchangeable-Al, N-NH4+, N-NO3- and plant dry weight, then the data analyzed using correlation and regression tests.  The results showed that giving coffee grounds with different doses of up to 5 ton ha-1 did not provide a significant relationship pattern on alteration of pH, exchangeable-Al, N-NH4+, N-NO3- in soil, also in plant dry weight.